Sports Training Methods of Highly Qualified Belt Wrestlers - Zulunkhojaev Marufjon Mamurjon ugli (Researchparks Publishing, 2022)
The article describes the methods of training highly qualified wrestlers in belt wrestling. The long-term training of highly qualified wrestlers provides information on the classification of three-stage models.